Investigating different methods for application of earthquake records in seismic evaluation of irregular RC bridges considering incident angles. (August 2021) - Tehrani, Payam; Ghanbari, Reza
Abstract: Seismic response of 9 regular and irregular four-span RC bridges with different configurations was studied using elastic and inelastic time history analyses. The influence of using different approaches for applying the ground motion records, considering the interaction of the orthogonal horizontal components of the ground motion records and their incident angles, was investigated. For this purpose, the records were applied to the structural models using three different methods and the results were compared. To investigate the influence of the directivity of the records on the mean seismic response, the records were applied at 19 different incident angles. The use of the 100–30 combination rule for prediction of the maximum response was also investigated. In addition, the results from linear and nonlinear analyses were compared and the maximum ductility demands and drift ratios were predicted. The results indicated that as the irregularity of the bridges increased, the seismic response became more coupled in the two principal directions and also became more sensitive to the incident angle of the records. It was also shown that when the mean seismic response was considered, the results were less sensitive to the incident angle compared to the case that the response from the individual records was considered.